2020
DOI: 10.1002/jso.26338
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node mapping with indocyanine green compared to blue dye tracer in gynecologic malignancies—A single center experience of 218 patients

Abstract: Background and Objectives To compare the detection rates of sentinel lymph nodes after converting the tracer technique from blue dye to indocyanine green (ICG). Methods Patients with uterine or cervical cancer were enrolled for sentinel lymph node (SLN) dissection. A total of 109 consecutive patients were analyzed and compared to a historical cohort of 109 consecutive patients with the sentinel blue dye technique. SLNs were analyzed by ultrastaging. Results The bilateral mapping rate of sentinel nodes was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The most common anatomical sites were the external iliac (45.8% on the right and 46.6% on the left) and obturator regions (20.9% and 25.6%, respectively). These results were consistent with those reported in the literature, where the rate of external iliac site SL was 32-59.3%, and obturator region was 18-25% [10,[17][18][19].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The most common anatomical sites were the external iliac (45.8% on the right and 46.6% on the left) and obturator regions (20.9% and 25.6%, respectively). These results were consistent with those reported in the literature, where the rate of external iliac site SL was 32-59.3%, and obturator region was 18-25% [10,[17][18][19].…”
Section: Discussionsupporting
confidence: 93%
“…The result of our study showed the overall SL detection rate of 88.8%, while bilateral detection rate was 68.2%. According to published data, the reported overall detection rate varied from 86% to 97.4%; however, bilateral detection rates were usually lower, and varied from 52% to 96% [5][6][7][8][9][10][11][17][18][19]. These results came from the trials where both robotic and laparoscopic approaches have been used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized non-inferiority trial of 180 patients with uterine and cervical cancer showed that, ICG detected 97% of the total lymph nodes dissected whereas blue dye identified only 47% ( 38 ). Recent research from Germany compared ICG with blue dye in EC and cervical cancer, as a result, ICG improved the DR (78% vs. 61%, p=0.006) and therefore decreased the LAD rate from 28% to 9% (p=0.001) when mapping failure occurs ( 39 ). However, the method relies on near-infrared device ( 40 ).…”
Section: The Technique Advances Of Slnmmentioning
confidence: 99%
“…In gynecological tumors, a single-center cohort of 218 patients found that indocyanine green (ICG) increased the detection rate of pelvic SLNs compared with blue dye ( 22 ). For detection with 99mTc dye, lymph nodes must emit radiation that exceeds a multiple of the preset background radiation intensity to be detected.…”
Section: Introduction To Sentinel Lymph Node Techniquesmentioning
confidence: 99%